Prediksi Kepribadian Berdasarkan Media Sosial Twitter Menggunakan Metode Naïve Bayes Classifier - A, Muhammad Ichsanudin; Irawan, Agung Susilo Yuda; solehudin, Arip (J-SAKTI (Jurnal Sains Komputer dan Informatika), 2021)
Analysis of a person's personality is very helpful as an assessment in various matters such as recruitment, career, health. The methods commonly used in personality analysis are interviews, observations, and questionnaire surveys. This study tries to provide a solution by simply using social media, namely twitter, by analyzing twitter user information data called tweets, this is to add to the method of personality analysis. The method used in this personality prediction research is to classify a tweet into 5 personality forms. The personality method used by the researcher is the Big Five Personality which consists of openness, conscientiousness, extraversion, agreeableness, and neuroticism with classification calculations using Naive Bayes. The result of this research is an accuracy of 42% with the highest class, namely Agreeableness.